Variance components and prediction of genetic values in rubber tree clones by the mixed model methodology (REM/BLUP) - Filho, Antonio Nascim Kalil; Resende, Marcos Deon Vilela de; Kalil, Geovanita Paulino da Costa (Pesquisa Agropecuaria Brasileira, 2000)
This paper aims to estimate genetic parameters and predict additive genetic and genotypic values from amazonian rubber tree clones for characteristics associated to rubber and latex quality based in genealogy of 15 clones and 250 ramets. The estimates from heritability in the wide sense (ha²) were 0.4152 and 0.6357 for dry rubber content (DRC) and plasticity after 30 minutes (P30), respectively, what makes possible to obtain high genetic gains by clonal selection. Clones IAN 873 and Fx 3899 presented the highest additive genetic and genotypic values for DRC, while clone IAN 6158 presented the highest genotypic values for P30 and plasticity retention index (PRI) characteristics.